Peningkatan Literasi Sains Siswa melalui Culturally Responsive- Project Based Learning (CR-PjBL) Terintegrasi Kearifan Lokal 'Sinonggi’ - Nur Hikmah; Muh. Idham Haliq (Alpatih Harapan Semesta, 2026)
This study aims to investigate the effectiveness of culturally responsive Project-Based Learning (CR-PjBL) integrated with Sinonggi local wisdom in improving students' scientific literacy. Based on a culturally responsive pedagogical framework, this study aims to bridge students' everyday cultural experiences with formal science learning to foster deeper understanding and engagement. A quasi-experimental design was used involving junior high school students, where the experimental group was taught using PjBL integrated with Sinonggi, while the control group received conventional teaching. Data collection techniques in this study were through observation, tests, and questionnaires. The instruments used in this study were multiple-choice questions (two levels), observation sheets, and student response questionnaires. The results showed that students exposed to culturally integrated PjBL showed a significantly higher increase in scientific literacy compared to students in the control group. Furthermore, students showed increased engagement, critical thinking, and the ability to apply science concepts in real-life contexts. The results of the independent sample T-Test obtained a sig. (2 tailed) of 0.00 < 0.05, which means there is a difference in the scientific literacy scores of students who are given learning experiences using Project-Based Learning (CR-PjBL) that is culturally responsive and integrated with Sinonggi local wisdom with the scores of students taught with conventional models. The N-Gain value obtained is 0.60, categorized as moderate, indicating that the PjBL Model integrated with 'Sinonggi' local wisdom is quite effective in improving students' scientific literacy. These findings indicate that integrating local knowledge such as Sinonggi into project-based science learning not only improves cognitive outcomes but also supports culturally meaningful learning experiences.